Investigation of chikungunya fever outbreak in Laguna, Philippines, 2012 - Ballera, Julius Erving (Western Pac Surveill Response J, 2015)
BACKGROUND: In July 2012, the Philippines National Epidemiology Center received a report of a suspected chikungunya fever outbreak in San Pablo City, Laguna Province, the first chikungunya cases reported from the city since surveillance started in 2007. We conducted an outbreak investigation to identify risk factors associated with chikungunya. METHODS: A case was defined as any resident of Concepcion Village in San Pablo City who had fever of at least two days duration and either joint pains or rash between 23 June and 6 August 2012. Cases were ascertained by conducting house-to-house canvassing and medical records review. An unmatched case-control study was conducted and analysed using a multivariate logistic regression. An environmental investigation was conducted by observing water and sanitation practices, and 100 households were surveyed to determine House and Breteau Indices. Human serum samples were collected for confirmation for chikungunya IgM through enzyme-linked immunosorbent assay. RESULTS: There were 98 cases identified. Multivariate analysis revealed that having a chikungunya case in the household (adjusted odds ratio [aOR]: 6.2; 95% confidence interval [CI]: 3.0–12.9) and disposing of garbage haphazardly (aOR: 2.7; 95% CI: 1.4–5.4) were associated with illness. House and Breteau Indices were 27% and 28%, respectively. Fifty-eight of 84 (69%) serum samples were positive for chikungunya IgM. CONCLUSION: It was not surprising that having a chikungunya case in a household was associated with illness in this outbreak. However, haphazard garbage disposal is not an established risk factor for the disease, although this could be linked to increased breeding sites for mosquitoes.